The Efficacy of Adobe Flash CS6-Based Interactive Learning Media in Enhancing Student Academic Performance - Hermawansa, Hermawansa; Bainamus, Putri Milanda; Mikaresti, Pamela; Ilahi, Bogy Restu; Susanto, Edy (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This study aims to Effectively Utilize Adobe Flash CS6-Based Interactive Learning Media in Improving the Learning Outcomes of State Junior High School Students 03 South Bengkulu. This research method is a descriptive quantitative experiment. The design that will be used is Design One Pretest-Posttest Group. The subjects of this study are 30 students of Grade seven B State Junior High School 03 South Bengkulu. The instrument used was 20 multiple-choice questions. The results of the study with paired sample test showedÂ that the valueÂ of asym sig. (2-tailed) of 0.00 < 0.05 so that it was rejected and accepted, which means that there is an effectiveness of interactive learning media based on adobe flash CS6 in improving student learning outcomes in the informatics subject of grade VII at SMP Negeri 3 South Bengkulu. It can be concluded that Adobe Flash CS6-based interactive learning media is effective in improving student learning outcomes in the informatics subject of grade VII at State Junior High School 03 South Bengkulu South Bengkulu. Keywords: Effectiveness, Learning Media, Adobe Flash CS6.